2016
DOI: 10.1007/s00520-016-3185-3
|View full text |Cite
|
Sign up to set email alerts
|

Race-based disparities in loss of functional independence after hysterectomy for uterine cancer

Abstract: Purpose Racial disparities in uterine cancer-related outcomes have been reported. The goal of this study was to determine if race, pre-operative body mass index (BMI) and medical comorbidities are predictors of loss of functional independence after surgery for uterine cancer. Methods Loss of independence was defined as a change from pre-operative functional independence, to a post-operative requirement of discharge to a post-care facility or death within the first 30 days following uterine cancer surgery. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…This observational cohort study provides novel insights regarding the duration of rehabilitation provided to older adults during a prolonged hospitalization for a range of diagnoses, and highlights large disparities in RD within a large safety‐net hospital that may contribute to differences in clinical and functional outcomes 25,33‐39 . We found that hospitalized older adults received about 1 hour of multidisciplinary rehabilitation per week.…”
Section: Discussionmentioning
confidence: 80%
“…This observational cohort study provides novel insights regarding the duration of rehabilitation provided to older adults during a prolonged hospitalization for a range of diagnoses, and highlights large disparities in RD within a large safety‐net hospital that may contribute to differences in clinical and functional outcomes 25,33‐39 . We found that hospitalized older adults received about 1 hour of multidisciplinary rehabilitation per week.…”
Section: Discussionmentioning
confidence: 80%